Revolutionizing renal biopsy: the emerging role of omics and artificial intelligence in nephrology - Alwahaibi, Nasar; Alwahaibi, Maryam (Frontiers in Medicine, 2025)
Renal biopsies remain indispensable in the diagnosis and management of renal diseases, offering critical histopathological insights that guide clinical decisions. Recent advances in artificial intelligence (AI) and multi-omics technologies have begun to transform renal pathology by enabling deeper molecular profiling, enhanced diagnostic precision, and personalized treatment strategies. Despite these promising developments, challenges such as implementation complexity, cost, and limited integration into routine clinical workflows have slowed widespread adoption. Notably, a significant gap exists in the literature regarding how these modern technologies are applied to maximize the diagnostic and prognostic value of renal biopsies. This mini-review highlights emerging applications of AI and omics in renal biopsy interpretation, emphasizing their potential to transform diagnostic approaches in precision nephrology. It aims to inform nephrologists, renal pathologists, and researchers about the evolving landscape of renal diagnostics, while highlighting areas for further clinical integration and interdisciplinary collaboration.